Putri Hijau Kearifan Lokal Masyarakat Melayu Sebagai Materi Pembelajaran BIPA - Deliani, Susy; Zulkarnain, Iskandar; Harahap, Muhammad Haekal; Zahara, Siti Fatimah (Linguistik : Jurnal Bahasa dan Sastra, 2025)
The Green Princess" is a Deli Malay folktale containing local wisdom that needs to be preserved and introduced to BIPA learners. Efforts to preserve culture can be conveyed by preparing materials for BIPA learners, so that the local wisdom of the Green Princess, containing educational and cultural values, can be introduced to BIPA learners. The local wisdom contained in the Green Princess folktale needs to be disseminated and introduced to foreign learners as BIPA learning material. Introducing local wisdom greatly helps foreign learners communicate with the local community. This study uses a qualitative method with a descriptive approach to gain an understanding of reality through an inductive thinking process. By engaging with the situations and phenomena of BIPA material preparation, learners can learn educational and cultural values through the Green Princess folktale, which serves as reading material in BIPA learning. This material contains the following educational values: 1) Truth values, 2) Religious values, 3) Moral values, and 4) Social values. This material also contains cultural values: 1) The relationship between humans and God, 2) The relationship between humans and other humans, 3) The relationship between humans and nature, and 4) The relationship between humans and their creations.